Políticas públicas voltadas para a qualidade da educação no ensino fundamental : inquietudes e provocações a partir do plano de desenvolvimento da educação - Quadros, Neli Helena Bender de (2008)
The quality of education theme of several currentdiscussions current proven as a great challenge for the current time of brasilian education, so that its discussion is a necessity. This study refers to political educationals expressed, in the development Plano de Desenvolvimento da Educação PDE, focused on the basic education. Its approach as objectives: know different ways of understanding of the term quality of education; discuss what educational politicals need to offer the public schools conditions to meet the problems related to the quality of education; identify the conception by quality of education expressed in the politicals of PDE and how they propose to face situations related to the results obtained by school in national evaluations. In addition to the construction of theoretical references, basis national authors and conferences at UNESCO, the information was obtained through explorative study by families with children study at public schools and focused on analysisby PDE. The emerging categories of this analysis pointed possibilities and limitations of the plan. This proposed actions and programmes to developbrasilian education. Makes a confrontation, necessary and urgent about questions related to quality of basic education. The study stand out some care to achieve, among others, especially those related to the extension of school session, intakes to financial education in schools, the fragility of national politicals about evaluations without considering social inequalities